Histochemical Comparision Of Fighting Capability Of Two Cock Breeds Of Odisha - Behera , B.R.; Das, R.K.; Palai, T.K.; Mishra, U.K.; Mandal , A.K. (Indian Journal of Veterinary Sciences and Biotechnology, 2011)
A comparative histochemical study between Aseel (Fighting cock) and Kalahandi (Nonfighting cock) was carried out. Glycogen and mucopolysaccharide content was studied which revealed higher amount of these compounds in almost all studied muscles and tendons in case of Aseel than that of Kalahandi cocks. Glycogen and carbohydrate which are instant source of energy available in muscle of Aseel make it capable to engage in burst activity for a longer period than its counterpart. These characteristics might attribute to the fighting ability of Aseel cocks.